How Do Pregnant Women in Surakarta Understand, Feel About, and Perceive Breastfeeding? A Qualitative Study Using Snowball Sampling - Argaheni, Niken Bayu; Putri, Noviyati Rahardjo; Sukamto, Ika Sumiyarsi; Kusmawati, Iffah Indri; Nugraheni, Angesti (Poltekkes Kemenkes Palu, 2025)
Breastfeeding is critical for the health of both mothers and infants, with global recommendations supporting exclusive breastfeeding for the first six months. This study aimed to examine the knowledge, attitudes, perceptions, and challenges faced by pregnant women in Surakarta.: Five women between 28 and 36 weeks of gestation were recruited using snowball sampling, and data were collected through in-depth interviews. Thematic analysis, conducted using NVivo 12. Revealed that while participants generally demonstrated a high level of preparedness for breastfeeding, challenges such as public discomfort, inconsistent readiness, and emotional uncertainties persisted. The support of their husbands was felt to be crucial by the participants in this study. However, as the study involved only five pregnant women, the findings should be interpreted with caution, and may not be generalizable to a wider population. Nonetheless, this study suggests that emphasis should be placed on addressing the individual needs of mothers and providing appropriate support interventions to help overcome emotional and logistical barriers, which could enhance effective breastfeeding practices in similar contexts.